Adsorption of Zn(II) in aqueous solution by activated carbons prepared from evergreen oak (Quercus rotundifolia L.). - Gómez-Tamayo, M Del Mar; Macías-García, Antonio; Díaz Díez, M Angeles; Cuerda-Correa, Eduardo M (Journal of hazardous materials, 2008)
In the present work activated carbons have been prepared from evergreen oak wood. Different samples have been prepared varying the concentration of the activating agent (H(3)PO(4)) and the treatment temperature. The yield of the process decreases with increasing phosphoric acid concentrations. Furthermore, high concentrations of activating agent lead to mainly mesoporous activated carbons to the detriment of the microporous texture. Treatment temperatures up to 450 degrees C lead to a progressive increase of the micro- and mesopore volumes. Values of specific surface area (S(BET)) as high as 1723 m(2) g(-1)have been obtained using appropriate phosphoric acid concentrations and treatment temperatures. The samples prepared have been successfully used in the removal of Zn(II) from aqueous solutions. From the adsorption kinetic data it may be stated that the equilibrium time is, in all cases, below 170 h. The adsorption process as a rule becomes faster as the mesopore volume and specific surface area of the samples increase. The adsorption isotherms in liquid phase point out that the adsorption capacity (n(0)(s)) and the affinity towards the solute (K(ci)) are higher for the sample showing the most developed mesoporous texture and surface area as well.
Keywords: Adsorption; Carbon; Carbon: chemistry; Hydrogen-Ion Concentration; Quercus; Solutions; Water Pollutants, Chemical; Water Pollutants, Chemical: chemistry; Water Purification; Water Purification: methods; Wood; Zinc; Zinc: chemistry